High tibial lateral closing wedge and opening wedge valgus osteotomy produce different effects on posterior tibial slope and patellar height - Ji, Songjie; Gao, Yuan; Zhang, Jun; Pan, Feng; Zhu, Kunzhi; Jiang, Xu; Zhou, Yixin (Frontiers in Surgery, 2023)
Objective To compare the clinical outcomes of performing a closed tibial high osteotomy with an open osteotomy and the changes in posterior tibia slope and patellar height. Methods were collected from three hundred and forty patients (440 knees) with high tibial osteotomy performed from January 2019 to January 2020. Forty patients (50 knees) had a lateral closed wedge tibial osteotomy (LCWHTO), and 300 patients (390 knees) had a medial open wedge tibial osteotomy (MOWHTO). The follow-up periods were 20.5 months and 19.9 months, respectively. At the final follow-up visit, both groups evaluated the Lysholm score and joint range of motion (ROM). Changes in preoperative and postoperative mechanical axis deviation (MAD), proximal medial tibial angle (MPTA), posterior tibial slope (PTS), and M-K index were compared between the two groups of patients. Results Lysholm scores were 79.6 ± 15. 6 preoperatively and 96. 0 ± 5.0 postoperatively in the LCWHTO group (p < 0.01); 83. 7 ± 16.0 preoperatively and 94. 3 ± 9.1 postoperatively in the MOWHTO group (p < 0.01). ROM was 136.0° ± 8.4° preoperatively and 133.2° ± 10.1° postoperatively in the LCWHTO group (p > 0.05)； 136.5° ± 8.4° preoperatively and 135.7° ± 9.3° postoperatively in the MOWHTO group (p > 0.05). the MAD was (26.5 ± 4.1) mm preoperatively and 0.3 ± 2.9 mm postoperatively in the LCWHTO group (p < 0.01); 21.8 ±6.5 mm preoperatively and -0.3±2.6 mm postoperatively in the MOWHTO group (p < 0.01) .The MPTA in the LCWHTO group was 75.3°±3.2° preoperatively and 89.5°±2. 4° postoperatively (p<0.01). 77.1°±3.0° preoperatively and 90.6°±2.7° postoperatively in the MOWHTO group (p<0.01). M-K index was 0.78±0.08 preoperatively and 0.79±0.07 postoperatively in the LCWHTO group (p>0.05). 0.78±0.05 before and 0.75±0.05 after surgery in the MOWHTO. 删除了: Does the high tibial osteotomy change the posterior tibia slope and patellar height？ 删除了: Hospital 删除了: , Fourth